2021
DOI: 10.3390/membranes11120958
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Distillation: Pre-Treatment Effects on Fouling Dynamics

Abstract: In the research reported in this paper, membrane distillation was employed to recover water from a concentrated saline petrochemical effluent. According to the results, the use of membrane distillation is technically feasible when pre-treatments are employed to mitigate fouling. A mathematical model was used to evaluate the fouling mechanism, showing that the deposition of particulate and precipitated material occurred in all tests; however, the fouling dynamic depends on the pre-treatment employed (filtration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The permeate flux of seawater showed a decrease through the DCMD process. The reason could be the fouling effect of seawater minerals and total dissolved solids (as mentioned in Figure 6e) in comparison to synthetic brine water [12,68,69]. It is important to highlight that in the case of an industrial scale module, the circulation pump generates a specific level of overpressure to induce deformation at the water-air interface, resulting in the wetting of the membrane.…”
Section: Evaluation Of Fabricated Membrane Performance In MD Applicationmentioning
confidence: 99%
“…The permeate flux of seawater showed a decrease through the DCMD process. The reason could be the fouling effect of seawater minerals and total dissolved solids (as mentioned in Figure 6e) in comparison to synthetic brine water [12,68,69]. It is important to highlight that in the case of an industrial scale module, the circulation pump generates a specific level of overpressure to induce deformation at the water-air interface, resulting in the wetting of the membrane.…”
Section: Evaluation Of Fabricated Membrane Performance In MD Applicationmentioning
confidence: 99%
“…Current techniques for fouling control are feed pretreatment and membrane cleaning [25,39,[43][44][45]. Some other approaches to mitigating fouling include fabricating new membranes with new designs and materials [41]; changing flow regimes; and developing antifouling membranes, including modifying the membrane surface, designing of new membrane modules, and the use of physical and chemical techniques [7,13,[45][46][47]. One of the main issues in membrane-based processes is fouling [7,24,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the pre-treatment of water before entering membrane systems was addressed in many studies to prolong and maintain membrane performance. Santos et al [ 4 ] evaluated the employment of pre-treatment before membrane distillation using experiments coupled with mathematical modeling. Their results showed that particulate and precipitated material deposition occurred in all tests.…”
mentioning
confidence: 99%